PENGEMBANGAN SELFI BUKIT TUMPENG SEBAGAI DAYA TARIK WISATA ALTERNATIF BERBASIS MASYARAKAT DI DESA LALANGLINGGAH - Putra, I Putu Aditya Prawira; Sumadi, Ketut; Nuriawan, I Nengah Alit (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
Tumpeng Hill Selfie Tour is one of the alternative tourist attractions in the tourist village of Lalanglinggah Banjar, Bukit Tumpeng Service, West Selemadeg District, Tabanan Regency. Seeing the potential that Selfi Bukit Tumpeng Tourism has, namely the good natural potential, as one of the alternative tourism options in Lalanglinggah village, the main driver emerged, namely the local community in collaboration with the Village Government. This needs to receive more attention so that the Selfi Bukit Tumpeng tourist attraction can develop optimally and sustainably as an asset in the future. This research is research using qualitative methods, using three theories, namely tourism management theory by Salah Wahab, participation theory by Cohen and Uphoff, and sustainable tourism theory by Sugiama. The aim of this research is to determine the management and development of the Selfi Bukit Tumpeng Tourist Attraction, so that when it is managed well and appropriately it will develop even better, so that it can be introduced more widely to tourists, as well as encouraging active participation of local communities in Lalanglinggah Village for the purpose of building the economic welfare of the local community in Lalanglinggah Village. Local communities certainly have an important role in developing Tumpeng Hill Selfie Tourism which uses Participation Theory through three stages, namely decision making, implementation and evaluation stages. These three components have produced solutions to overcome the problem of "Developing management of Tumpeng Hill Selfie Tourism after the Covid-19 pandemic" in order to create sustainable tourism.